Menggali Potensi Industri Kreatif Batik, Analisis Perkembangan dan Peluang di Daerah Istimewa Yogyakarta - Mutiara Nur Azqia; Ayu Wandira; Dita Prastari; Lia Kusumawati (Jurusan Pendidikan Geografi Universitas Negeri Manado, 2024)
Yogyakarta Batik is a creative industry produced by local craftsmen. This industry faces various challenges such as limited supply of raw materials, capital, and traditional promotion. However, this industry has a wide market opportunity because of its cultural heritage and traditional arts. This industry can grow through design innovation, collaboration, and tax incentives. The challenges include competition, consumer preferences, and raw material prices. To develop this industry, it is necessary to strengthen partnerships, digital marketing, skills training, sustainable innovation, and exports. Giriloyo Hamlet, located in Imogiri District, is the largest center for hand-drawn batik in the region and a place for the Giriloyo hand-drawn batik association.